(untitled) (Chemical Engineering Research Bulletin, 2009)
Carbon prepared from the epicarp of Ricinus communis was used to remove a textile dye (methylene blue (MB)) from an aqueous solution by adsorption technique under varying conditions of agitation time, dye concentration, adsorbent dose and pH. Adsorption depended on solution pH, dye concentration, carbon concentration and contact time. Adsorption followed both Langmuir and Freundlich isotherm models. The adsorption capacity was found to be 62.5mg/g at a neutral pH of 7 for the particle size of 125-250 µm at room temperature (32±2°C). The kinetics of adsorption of MB obeys Pseudo-first order. The results in this study indicated that activated carbon from Ricinus communis was an attractive candidate for removing cationic dyes from the dye wastewater. Keywords: Epicarp, Ricinus communis, Adsorption, Methylene blue, Kinetics DOI = 10.3329/cerb.v13i1.2518 Chemical Engineering Research Bulletin 13 (2009) 1-5